The African Continental Free Trade Area : Potential Economic Impact and Challenges - Abrego, Lisandro (Staff Discussion Notes; Staff Discussion Notes ;, 2020)
Political momentum towards Africa-wide free trade has been intensifying. In March 2018, over 40 countries signed the African Continental Free Trade Area (AfCFTA) agreement. Once fully implemented, the AfCFTA is expected to cover all 55 African countries, with a combined GDP of about USD 2.2 trillion. This SDN takes stock of recent trade developments in Sub-Saharan Africa and assesses the potential benefits and costs of the AfCFTA, as well as challenges to its successful implementation. In addition to increased trade flows both in existing and new products, the AfCFTA has the potential to generate substantial economic benefits for African countries. These benefits include higher income arising from increased efficiency and productivity from improved resource allocation, higher cross-border investment flows, and technology transfers. Besides lowering import tariffs, to ensure these benefits, African countries will need reduce other trade barriers by making more efficient their customs procedures, reducing their wide infrastructure gaps, and improving their business climates. At the same time, policy measures should be taken to mitigate the differential impact of trade liberalization on certain groups as resources are reallocated in the economy and activities migrate to locations with comparatively lower costs.